Understanding drivers of sorghum variety adoption and seed supply pathways in market-linked systems in lower Eastern Kenya: value-chain actor engagement - Gichuru, Lilian; Kisilu, Rachael K.; Mutinda, Nicxon; Wambua, John; Mutinda, Urbanus (CIMMYT, 2025)
This study examines the sorghum seed and grain system in Lower Eastern Kenya, with a focus on how farmers, extension agents, cluster seed producers, and the brewing industry interact to shape the dynamics of variety adoption, seed supply, and market performance. Data were collected through farmer focus group discussions, extension officer interviews, cluster seed producer interviews, and an in-depth interview with the sorghum procurement team at Kenya Breweries Limited (KBL). Farmers in Mtito Andei in Makueni County, and neighboring areas cultivate a mix of older open-pollinated varieties such as Gadam, Serena, Seredo, and Kari Mtama 1, alongside the newly released Pato 1. Historically, variety choices have been shaped by bird damage, drought stress, and inconsistent access to quality seed, household consumption, and availability of markets. Pato 1 has rapidly emerged as the preferred new variety due to its reduced bird damage, larger grain, early maturity, strong fodder potential, and the existence of a guaranteed market from breweries. Extension officers confirm that the presence of a reliable buyer is now the strongest driver of varietal change, surpassing agronomic considerations alone. Seed supply, however, remains a significant bottleneck. Farmers rely primarily on grodealers and saved seed with occasional supply from the Kenya Agricultural and Livestock Research Organization (KALRO) Seeds. Across the respondents, challenges include untimely seed availability, mixed or poor-quality seed, high prices, farmers’ locational production remoteness, and difficulty in obtaining sufficient quantities. Cluster seed producers trained by KALRO play a valuable role in local seed availability and benefit from seed advancement, where KALRO provides recovery parent seeds at planting. Nevertheless, their productivity is constrained by erratic rainfall, high labour costs, and lack of essential equipment such as threshers. Kenya Breweries Limited (KBL) exerts major influence over the sorghum system due to its contract engagement and strict procurement requirements. The brewery prioritises varieties that meet clear thresholds for grain size, extract potential, moisture content, leanliness, and storage stability. Older varieties such as Gadam often fail to meet these standards due to glume attachment, poor storability, and higher pest damage. Farmers’ inability to meet brewery standards consistently stems from poor land preparation, weak soil nutrition management, and limited postharvest handling skills. Fragmented aggregation structures also contribute to inconsistent quality and unreliable supply volumes. Additionally, breweries anticipate a growing role for sorghum hybrids (such as AGV Kuzo) due to their high yield advantage and favorable brewing characteristics. However, successful adoption will depend on targeted capacity building and stronger seed distribution systems. Overall, the study reveals a sorghum system in transition from subsistence to commercial crop. Marketlinked demand, seed system performance, and variety traits are becoming more aligned, yet persistent constraints in seed access, agronomic capacity, and grain quality management continue to limit farmers’ ability to fully benefit from commercial opportunities. Addressing these constraints through targeted seed system strengthening, improved gronomy, and enhanced market coordination will be essential for unlocking the potential of sorghum in Lower Eastern Kenya.